2009
DOI: 10.1086/644640
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Cold Shock Increases Adherence ofMoraxella catarrhalisto and Secretion of Interleukin 8 in Human Upper Respiratory Tract Epithelial Cells

Abstract: Moraxella catarrhalis, a major nasopharyngeal pathogen of the human respiratory tract, is exposed to rapid and prolonged downshifts of environmental temperature when humans breathe cold air. In the present study, we show that a 26 degrees C cold shock up-regulates the expression of UspA1, a major adhesin and putative virulence factor of M. catarrhalis, by prolonging messenger RNA half-life. Cold shock promotes M. catarrhalis adherence to upper respiratory tract cells via enhanced binding to fibronectin, an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…In addition, children of 3~5 y old are in the nursery period, the susceptible environment of kindergartens and immune function which have not been well developed yet cause it prone to bacterial infection of respiratory tract. In all age groups, detection rate of SP come first, especially in the age group 3~5 y old, it was the highest and the lowest in <6 months group, which were basically consistent with the reports from Cai et al [19] and Sun et al [21][22][23]. Previous reports have suggested that HI and E. coli infections are mainly seen in children under 1 y old [20,23,24].…”
Section: Resultssupporting
confidence: 89%
“…In addition, children of 3~5 y old are in the nursery period, the susceptible environment of kindergartens and immune function which have not been well developed yet cause it prone to bacterial infection of respiratory tract. In all age groups, detection rate of SP come first, especially in the age group 3~5 y old, it was the highest and the lowest in <6 months group, which were basically consistent with the reports from Cai et al [19] and Sun et al [21][22][23]. Previous reports have suggested that HI and E. coli infections are mainly seen in children under 1 y old [20,23,24].…”
Section: Resultssupporting
confidence: 89%
“…The M. catarrhalis lipooligosaccharides (LOS) (68) and the outer membrane protein UspA1 might be involved in stimulating the secretion of IL-8 in vitro (57), and MID/Hag might be involved in B-cell activation (47,67). Importantly, serum samples from COPD patients who had recently cleared M. catarrhalis infection are reactive to M. catarrhalis LOS (53) and MID/Hag (40), indicating that M. catarrhalis extracellular components may contribute to the production of inflammatory disease.…”
Section: Figmentioning
confidence: 99%
“…The ability of M. catarrhalis to adhere to and invade human Detroit 562 epithelial cells in vitro was measured as described previously (13,27,28). Each strain was analyzed in triplicate in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Such rapid variation of temperature induces adaptive events in the residential upper respiratory tract flora that may contribute to the transition from asymptomatic colonization to infection. Our previous in vitro studies demonstrated that a 26°C cold shock upregulates the expression of important virulence traits, such as adherence to epithelial cells, iron acquisition, complement resistance, and immune evasion (12)(13)(14).Adaptive resistance also involves a temporary increase in the ability of a bacterium to survive exposure to antimicrobials due to alterations in gene/protein expression as a result of an environmental trigger, e.g., temperature, stress, nutrient conditions, or subinhibitory levels of the antibiotics themselves (15). One of the main antimicrobial resistance strategies of bacteria is altered porin expression to limit intracellular access of antibiotics.…”
mentioning
confidence: 99%
See 1 more Smart Citation